2005
DOI: 10.1007/s10600-005-0142-7
|View full text |Cite
|
Sign up to set email alerts
|

Aldimines of Cardenolides and Cardenolide-Glycosides

Abstract: New aldimines were synthesized from the cardenolide strophantidin and cardenolide-glycosides erysimin and cymarin and included morpholine, nitrile, pyridine, furan, hydroxy-and methoxyphenyl, piperidine, and other derivatives. An effective modified method for synthesizing aldimines was proposed. 52 new compounds were synthesized. Their structures were confirmed by IR and PMR spectra and elemental analysis.We previously reported [1, 2] the synthesis of eight aldimines of strophantidin, some of which were slig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…These data agree with the literature [3] relative to the stereochemistry of aldimines of cardenolides. Figure 1 shows the PMR spectrum.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…These data agree with the literature [3] relative to the stereochemistry of aldimines of cardenolides. Figure 1 shows the PMR spectrum.…”
supporting
confidence: 92%
“…We believe as before [3] that this is the trans-isomer. This is consistent with the PMR spectra and the ability of the obtained azomethines to form complexes with Cu ions.…”
mentioning
confidence: 57%
“…Previous studies of transformed cardiosteroids have shown that aldimines of cardenolides have been shown to be low-toxic cardiotonics (e.g., adamantyliminostrophantidin) [3]. In this regard, it seemed advisable to continue these studies, having received a wider set of new substances with subsequent pharmacological screening and the detection of the most promising in practical terms, physiologically active derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…In the synthesis of aldimines of cardenolides, we had that comparatively exceptional case when two types of isomerismconformational (conformers) and geomet-ric (cis-trance or syn-anti (Fig. 1)) took place simultaneously [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation